EXPLORATORY STUDY ON THE IMPACT OF MICROTEACHING COURSE ON MENTAL HEALTH OF SIXTH-SEMESTER STUDENTS IN THE ENGLISH EDUCATION PROGRAM AT UNIVERSITY OF RIAU KEPULAUAN - Pratiwi, Septiani Indah; Sari, Nur Ramidah; Maharani, Deswita Aulia; Mustapa, Zainal; Rahmawati, Alivia; Ramadanti, Tiara; Afrinal, Hendri; Wibowo, Agung Edy; Ratnasari, Sri Langgeng; Zulkifli, Zulkifli (JURNAL DIMENSI, 2025)
This study aims to determine the impact of the microteaching course on the mental health of sixth-semester students in the English Education program at University of Riau Kepulauan. Microteaching is a required course for future teachers to prepare them to teach using simulation methods on a small scale before students engage in teaching practice in real classroom settings. The study used a quantitative approach with an explanatory design. Thirty sixth-semester students who have completed the microteaching course participated in this study. Data were collected through the Behavioral Health Measure (BHM) questionnaire, which measures three indicators, such as well-being, psychological symptoms, and life functioning. The results of the study showed that the students' mental health was in the good category, with an average score of 71,17%. 33,3% of students had excellent mental health, and only 3,4% experienced moderate stress. The psychological symptoms indicators showed the highest score (2,88), followed by well-being (2,83) and life functioning (2,75). These findings indicate that the microteaching course does not have a significant negative impact on students' mental health. Students were able to manage the anxiety and pressure that arose during the learning process well. This study also highlights the importance of ongoing psychological monitoring and institutional support throughout performance-based academic learning processes.